DAMPAK PSIKOLOGIS BAGI ANAK PIDANA YANG DITEMPATKAN DI LAPAS DEWASA - Natasya Monica Paskah; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
Penitentiary is a place for convicts who break the law to be fostered with the aim that they are aware of their mistakes so that they do not repeat their crimes, and can be accepted by society again. Anyone who commits a crime under the applicable provisions and regulations will be subject to imprisonment for men, women, adults and children, but the placement is carried out separately. In this case Law no. 22 of 2022 concerning Corrections has regulated the placement of convicts according to their categories, but there are still criminal children who are not placed according to the rules, for example in the Class I Detention Center in Depok which is supposed to be for Adult Prisoners but there are still 3 criminal children who are placed there, of course this will psychological impact on children, because they should be placed in LPKA.